AN ANALYSIS OF COGNITIVE LINGUISTICS TENETS IN AN ENGLISH FOR SPECIFIC PURPOSES TEXTBOOK - Dwi Wahyuningtyas (Journey: Journal of English Language and Pedagogy, 2022)
In English language teaching, cognitive linguistics has played an important role in classroom activities. This can be the depicted in the use of the textbooks. In this study, the textbook used is English for international Relations book, a part of English for Specific Purposes series published by Universitas Muhammadiyah Malang. Two of the features that chime cognitive linguistics principles are metaphors and categorization leading to prototype. Meanwhile, one of the clashes that is apparent in the textbook is the use of English which is unnatural, one of the factors is the textbook is used in a non-English speaking country. In the end, there are some suggestions on how to deal with the tenets of cognitive linguistics for the features that still clash with the principles of cognitive linguistics. First, it can be done by introducing some words that may have different meanings if they are added with different prepositions. The second example might be adjusting the use of the pictures and illustrations with the text and context. Also, the learners are suggested to know the patterns of the target language as they are different from their mother tongue.